1987
DOI: 10.1007/bf01422667
|View full text |Cite
|
Sign up to set email alerts
|

Method for direct measurement of the film tension of black foam films at various capillary pressures

Abstract: Abstract:A new experimental method to directly measure the film tension of black foam films is developed on the basis of the Laplace equation. The method allows the determination of the tension of curved (spherical) fdms with various radii and capillary pressures. Measurements with Newton black films from sodium dodecyl sulphate aqueous solution have been carried out. The results show that in the studied range of curvature radii (70 + 360 ~m) the film tension does not depend on the curvature and the capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…This result can be explained with the high solubility of SDS and with the great facility of sorption and desorption of this surfactant from the film surfaces. As previously reported [22,39,40], the results obtained by means of the same method for films of different solutions of phospholipids and mixtures of phospholipids differ from those for the SDS film; a hystheresis of the contact angle is observed for all these films. The results obtained in the present study for the time dependence of 2θ for the ALG, BLG, and BSA films are shown in Figs.…”
Section: Dynamic Contact Angle Of Protein Black Filmssupporting
confidence: 65%
“…This result can be explained with the high solubility of SDS and with the great facility of sorption and desorption of this surfactant from the film surfaces. As previously reported [22,39,40], the results obtained by means of the same method for films of different solutions of phospholipids and mixtures of phospholipids differ from those for the SDS film; a hystheresis of the contact angle is observed for all these films. The results obtained in the present study for the time dependence of 2θ for the ALG, BLG, and BSA films are shown in Figs.…”
Section: Dynamic Contact Angle Of Protein Black Filmssupporting
confidence: 65%
“…All of these approaches make use of a spherical drop or bubble and relate the simple geometric parameters of the sphere to the Laplace equation of capillarity to calculate film tension. Platikanov et al , reported an experimental method for direct measurement of the film tension of black foam films. Their foam films are obtained in the form of a spherical semibubble, whose radius of curvature is determined from microphotographs and the capillary pressure is measured by a manometer.…”
Section: Discussionmentioning
confidence: 99%
“…It is the purpose of this work to design an experiment that will record the dynamics of film thinning and film rupture, i.e., to develop a new methodology for measuring film tension. This is significant since, presently, compared to the number of techniques for measuring interfacial tension, only a small number of methods have been developed for measuring film tension. All of these approaches make use of a spherical drop or bubble and relate the simple geometric parameters of the sphere to the Laplace equation of capillarity in order to calculate film tension.…”
Section: Introductionmentioning
confidence: 99%